2021
DOI: 10.1021/acsbiomaterials.0c01716
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Review of Silk Scaffolds in Musculoskeletal Tissue Engineering Applications in the Recent Decade

Abstract: During the past decade, various novel tissue engineering (TE) strategies have been developed to maintain, repair, and restore the biomechanical functions of the musculoskeletal system. Silk fibroins are natural polymers with numerous advantageous properties such as good biocompatibility, high mechanical strength, and low degradation rate and are increasingly being recognized as a scaffolding material of choice in musculoskeletal TE applications. This current systematic review examines and summarizes the latest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 213 publications
0
18
0
Order By: Relevance
“…Polysaccharides and protein polymers, such as chitin 28 , alginate 29 , hyaluronic acid 30 , 31 , silk 32 , 33 , and keratin 9 display biochemical guidance for cell migration, overcoming the lack of targeting for the attachment, typical of the aforementioned synthetic polymers 34 . Indeed, the hydroxyl groups present in polysaccharides and the fibronectin-specific amino acid sequences (RGD: Arginine–Glycine–Aspartic acid, and LDV: Leucine-Aspartic acid-Valine) displayed by protein-based biomaterials have proven to be extremely important for a successful cell adhesion 35 , 36 .…”
Section: Introductionmentioning
confidence: 99%
“…Polysaccharides and protein polymers, such as chitin 28 , alginate 29 , hyaluronic acid 30 , 31 , silk 32 , 33 , and keratin 9 display biochemical guidance for cell migration, overcoming the lack of targeting for the attachment, typical of the aforementioned synthetic polymers 34 . Indeed, the hydroxyl groups present in polysaccharides and the fibronectin-specific amino acid sequences (RGD: Arginine–Glycine–Aspartic acid, and LDV: Leucine-Aspartic acid-Valine) displayed by protein-based biomaterials have proven to be extremely important for a successful cell adhesion 35 , 36 .…”
Section: Introductionmentioning
confidence: 99%
“…Silk fibroin (SF) of Bombyx mori ( B. mori ) silkworm, a U.S. Food and Drug Administration (FDA)-approved biomaterial, has been widely used in tissue engineering applications due to its wide range of properties including good biocompatibility, excellent mechanical strength, adjustable degradation, and non-inflammatory by-products [ [13] , [14] , [15] ]. Among the multiple SF scaffolds developed for osteochondral tissue engineering, SF hydrogels have gained considerable attention due to their high-water content and 3D porous structure which are similar to the natural extracellular matrix (ECM) [ 16 , 17 ]. Previous studies have shown that functionalized SF hydrogels could regulate stem cell behaviors such as cell migration, proliferation, and differentiation [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…The degummed silk (i.e., SF) has long been recognized as a promising biomaterial and has been widely used for tissue engineering applications. We and other researchers have developed various formats of SF scaffolds for the repair and regeneration of bone, cartilage, skin, cornea, etc (9)(10)(11)(12). In contrast, SS was previously regarded as a waste material during degumming and was found to cause immunological responses when combined with SF (13).…”
Section: Introductionmentioning
confidence: 99%